A nano-power-generating absorbable material, preparation method and absorbable nano-power-generating ligament repair prosthesis
By adopting the nano-power-absorbing material consisting of the nano-power generation fiber composed of a chitosan nano-nano-fiber and hydroxyl-based-hydroxyl-based pentalate, solve the problem of poor absorption performance of nano-power wire wires in existing technologies, and achieve efficient efficiency The ligament restoration and the renewal of the body sensation.
Patent Information
- Application Number
- CN202410285034.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-03-13
AI Technical Summary
In the prior art, the nano-power wires for ligament repair in clinically applied ligament have poor absorption performance and are difficult to meet clinical needs.
A nano-power-generating absorbable material is used, which is composed of chitosan nanofibers and hydroxybutyric acid-hydroxyvaleric acid copolyester sheathed fibers. It is prepared through electrospinning and melt spinning technology and has excellent absorbable properties. and mechanical properties.
This nano-power-generating absorbable material can effectively reconstruct the proprioceptive circuit. After being used as a suture to sew the main body to the ligament defect area, its mechanical properties meet the standard requirements and has no interference with the brain, significantly improving the absorbable performance of ligament repair.
Smart Images

Figure CN118615488B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medical materials, and in particular relates to a nano-power generation absorbable material, a preparation method and an absorbable nano-power generation ligament repair prosthesis. Background Art
[0002] After anterior cruciate ligament (ACL) rupture, mechanical stability decreases, proprioceptive afferent dysfunction occurs, central nervous system plasticity (CNSP), gait and movement posture abnormalities occur, and knee osteoarthritis occurs early. The pain caused by this seriously affects the patient's sports and mental health, greatly reducing the quality of life. Although conventional ACL reconstruction surgery (autologous or allogeneic tendon reconstruction, artificial ligament reconstruction) can increase the mechanical stability of the knee joint, it is difficult to fundamentally restore the proprioceptive afferent function of the ACL, and then it is difficult to avoid CNSP. This CNSP is not only a result, but also a cause of ACL injury, forming a vicious circle. Therefore, CNSP is crucial for the rehabilitation of ACL injury.
[0003] The development of materials science has opened a door for nerve repair and regeneration. On the one hand, various biological and non-biological nerve conduits have achieved gratifying results in basic and clinical research on peripheral nerve regeneration. Among them, chitosan has become an ideal material for constructing artificial nerve grafts due to its good adsorption, permeability, plasticity, biocompatibility and biodegradability. On the other hand, tissue regeneration takes time. During the time waiting for successful tissue regeneration, the number of ACL proprioceptors decreases, the morphology becomes abnormal, the function decreases, and the subsequent remodeling of the central nervous system is inevitable. During this period, new materials are needed that can collect mechanical energy as the joint moves, convert it into electrical energy, meet the requirements of sensing the deformation of the knee joint during movement, and generate electrical impulses for upload, simulate and replace the ACL proprioception, and restore the neural circuit.
[0004] In the prior art, although the nano-generating wires used in clinical ligament repair can meet the mechanical performance requirements, their absorbability is poor. Therefore, it is urgent to develop a nano-generating absorbable material with good absorption performance, satisfactory mechanical properties, and no interference with the brain. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a nano-power-generating absorbable material, a preparation method and an absorbable nano-power-generating ligament repair prosthesis. The nano-power-generating absorbable material can be used to reconstruct the proprioceptive circuit, has the characteristic of being absorbable, and is closer to clinical application. The nano-power-generating absorbable material is applied to the absorbable nano-power-generating ligament repair prosthesis. After it is used as a suture to suture the main body and the ligament defect area, its mechanical properties can meet the standard requirements.
[0006] The first object of the present invention is to provide a nanometer power generation absorbable material, wherein the diameter of the nanometer power generation absorbable material is 400-600 μm, the elongation at break is 10-20%, the tensile strength is 40-60 MPa, and the output electrical stimulation voltage is 0.5-2V.
[0007] The second object of the present invention is to provide an absorbable nano-electric ligament repair prosthesis, comprising:
[0008] main body;
[0009] The stretching part is the above-mentioned nano-power generation absorbable material, and the stretching part is used to sew the main body and the ligament defect area.
[0010] Further, the main body is configured to pass through the ligament defect area and form two support parts located on both sides of the ligament defect area, each of the support parts includes a connecting section connected to the ligament defect area and a fixing section extending in a direction away from the ligament defect area, and the fixing section is configured to be connected to the bone;
[0011] The stretching portion includes two traction lines respectively connecting the two support portions, one of the traction lines is used to sew the connecting segment of one of the support portions to the ligament defect area, and passes through the ligament defect area to be connected to the fixed segment of the other support portion, and the other traction line is used to sew the connecting segment of the other support portion to the ligament defect area, and passes through the ligament defect area to be connected to the fixed segment of one of the support portions.
[0012] The third object of the present invention is to provide a method for preparing a nano-power generation absorbable material, comprising the following steps:
[0013] Providing chitosan nanofibers;
[0014] Winding the chitosan nanofibers onto a metal wire to form a preassembled core fiber;
[0015] Providing hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber;
[0016] The hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber is coated on the preassembled core fiber to form the nano-power generation absorbable material.
[0017] Furthermore, the method for providing the chitosan nanofibers comprises:
[0018] preparing a chitosan precursor solution;
[0019] The chitosan precursor solution is injected into a first spinning machine for electrostatic spinning.
[0020] Furthermore, the method for preparing the chitosan precursor solution comprises:
[0021] Chitosan powder with a molecular weight of 100000-110000 and a deacetylation degree of ≥95% is added into a dichloromethane-trifluoroacetic acid mixed solvent at a mass concentration of 8-10wt% until it is completely dissolved.
[0022] Furthermore, the external positive and negative voltages of the electrospinning are 8.5-9.5 kV, and the distance between the positive and negative electrodes is 15-20 cm;
[0023] The feeding rate of the chitosan precursor solution is 0.025-0.035 mL / h;
[0024] The rotation speed of the metal funnel of the first spinning machine is 600-800 rpm, and the rotation speed of the winding roller of the first spinning machine is 25-30 rpm.
[0025] Furthermore, the metal wire is a magnesium wire.
[0026] Further, the method for providing the hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber comprises:
[0027] Adding dry and anhydrous hydroxybutyric acid-hydroxyvaleric acid copolyester powder into chloroform until it is completely dissolved to obtain a hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution;
[0028] The hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution is injected into a second spinning machine for melt spinning.
[0029] Further, the processing temperature of the melt spinning is 230-260°C;
[0030] The feeding rate of the hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution is 0.25-0.3 kg / h;
[0031] The winding machine speed of the second spinning machine is 20-25m / min.
[0032] The above technical solution of the present invention has the following advantages compared with the prior art:
[0033] 1. The absorbable nanomaterial for power generation in the embodiment of the present invention has piezoelectric properties, which can help the defective ligament to rebuild the proprioceptive circuit. After the absorbable nanomaterial for power generation is used as a suture to suture the main body and the ligament defect area, it has no interference effect on the brain, which is close to clinical application.
[0034] 2. The absorbable nano-power-generating material of the embodiment of the present invention is used to suture and connect the main body with the ligament defect area, thereby repairing ACL damage. The absorbable nano-power-generating material is applied to absorbable nano-power-generating ligament repair prosthesis. After the absorbable nano-power-generating material is used as a suture to suture the main body with the ligament defect area, the mechanical properties can meet the standard requirements.
[0035] 3. The absorption performance of the absorbable nano-power-generating material of the embodiment of the present invention is better than the nano-power-generating wire used in clinical ligament repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0037] Figure 1 This is a schematic structural diagram of an absorbable nano-electric ligament repair prosthesis according to an embodiment of the present invention;
[0038] Figure 2 This is a before-and-after comparison diagram of verifying the absorbability of the absorbable nano-power-generating material of an embodiment of the present invention when it is used as a suture thread;
[0039] Figure 3 This is a comparison diagram of the brain fMRI test results of the common silk thread of Comparative Example 1 and Comparative Example 2 on the New Zealand white rabbit animal model;
[0040] Figure 4 This is a comparison diagram of brain fMRI test results of New Zealand white rabbit animal model using absorbable nano-power generation materials of Comparative Example 1 and the embodiment of the present invention;
[0041] Figure 5 This is a comparison diagram of the brain fMRI test results of the absorbable nanomaterial for power generation in Comparative Example 2 and the embodiment of the present invention on a New Zealand white rabbit animal model;
[0042] Figure 6 This is a comparison chart of the Western Blot results of the absorbable nano-power generation materials in Comparative Example 1, Comparative Example 2 and the embodiment of the present invention on the ASIC3 protein in the ligament tissue of the New Zealand white rabbit animal model;
[0043] Figure 7 This is a comparison chart of the Western Blot results of ASIC3 protein in the brain tissue of New Zealand white rabbit animal model using comparative example 1, comparative example 2 and the absorbable nano-power generation material of the embodiment of the present invention;
[0044] Figure 8 This is a comparison chart of the sciatic nerve action potential results of the absorbable nanomaterials for power generation in Comparative Example 1, Comparative Example 2 and the embodiment of the present invention on the New Zealand white rabbit animal model;
[0045] Fig. 9 This is a flow chart for preparing the absorbable nano-power generation material according to an embodiment of the present invention.
[0046] Reference numerals:
[0047] 100. Main body; 110. Femoral supporting part; 111. Femoral connecting section; 112. Femoral fixing section; 120. Tibial supporting part; 121. Tibial connecting section; 122. Tibial fixing section; 210. Femoral traction line; 220. Tibial traction line; 310. Femoral compression fixing screw; 320. Tibial compression fixing screw; 1. Femur; 2. Tibia; 3. Ligament defect area. DETAILED DESCRIPTION
[0048] The following is combined with Figure 1-9 The present invention is further described with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0049] The object of the present invention is to provide a nanometer power generation absorbable material, wherein the diameter of the nanometer power generation absorbable material is 400-600 μm, the elongation at break is 10-20%, the tensile strength is 40-60 MPa, and the output electrical stimulation voltage is 0.5-2V.
[0050] Another object of the present invention is to provide an absorbable nano-power generation ligament repair prosthesis, comprising a main body 100 and a distraction part, wherein the distraction part is a nano-power generation absorbable material having the above-mentioned properties, and the distraction part is used to suture the main body 100 with the ligament defect area 3. In other words, the distraction part having the above-mentioned properties is used as a suture line to suture the main body 100 with the ligament defect area 3, which can play a role in repairing ACL damage, and after the main body 100 and the ligament defect area 3 are sutured with the distraction part having the above-mentioned properties as a suture line, the mechanical properties can meet the standard requirements.
[0051] As an embodiment of the present invention, the main body 100 is configured to pass through the ligament defect area 3 and form two support parts located on both sides of the ligament defect area 3, each support part includes a connecting segment connected to the ligament defect area 3 and a fixed segment extending in a direction away from the ligament defect area 3, the fixed segment is configured to be connected to the bone, and the distraction part includes two traction lines respectively connecting the two support parts, one of which is used to sew the connecting segment of one of the support parts to the ligament defect area 3, and pass through the ligament defect area 3 to connect with the fixed segment of the other support part, and the other is used to sew the connecting segment of the other support part to the ligament defect area 3, and pass through the ligament defect area 3 to connect with the fixed segment of one of the support parts.
[0052] That is to say, Figure 1 As shown, for the convenience of explanation, taking the use of the absorbable nano-power generation material of an embodiment of the present invention as a suture thread, taking the suture of the damaged ligament and the main body 100 between the femur 1 and the tibia 2 as an example, a cavity is formed between the femur 1 and the tibia 2, the ligament defect area 3 is located in the cavity between the femur 1 and the tibia 2, a femoral compression fixing screw 310 and a tibial compression fixing screw 320 are respectively provided on the femur 1 and the tibia 2, one end of the main body 100 extends toward the femur 1 and is connected to the femur 1 through the femoral compression fixing screw 310, and the other end of the main body 100 extends toward the tibia 2 and is connected to the tibia 2 through the tibial compression fixing screw 320. For further convenience of explanation, the main body 100 located on the side close to the femur 1 is called a femoral supporting portion 110, and the end of the femoral supporting portion 110 close to the ligament defect area 3 is the femoral connecting section 111 connected to the ligament defect area 3, and the end extending in the direction away from the ligament defect area 3 is the femoral fixing section 112; the main body 100 located on the side close to the tibia 2 is called a tibial supporting portion 120, and the end of the tibial supporting portion 120 close to the ligament defect area 3 is the tibial connecting section 121 connected to the ligament defect area 3, and the end extending in the direction away from the ligament defect area 3 is the tibial fixing section 122. Correspondingly, the traction line for suturing the femoral connection segment 111 of the femoral supporting portion 110 and the ligament defect area 3 is a femoral traction line 210, and the femoral traction line 210 passes through the ligament defect area 3 and is connected to the tibial fixation segment 122 of the tibial supporting portion 120. The traction line for suturing the tibial connection segment 121 of the tibial supporting portion 120 and the ligament defect area 3 is a tibial traction line 220, and the tibial traction line 220 passes through the ligament defect area 3 and is connected to the femoral fixation segment 112 of the femoral supporting portion 110. That is to say, after the femoral traction line 210 connects the femoral supporting portion 110 with the ligament defect area 3, it extends to the tibial supporting portion 120, thereby pulling the femoral supporting portion 110 and improving the connection strength. Correspondingly, after the tibial traction line 220 connects the tibial supporting portion 120 with the ligament defect area 3, it extends to the femoral supporting portion 110, thereby pulling the tibial supporting portion 120 and further improving the connection strength.
[0053] Another object of the present invention is to provide a method for preparing a nanometer power generation absorbable material, comprising the following steps: Fig. 9 As shown, chitosan nanofibers are provided; chitosan nanofibers are wound around metal wires to form preassembled core fibers; hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fibers are provided; hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fibers are coated on the preassembled core fibers to form nano-power generation absorbable materials. That is to say, with the metal wire as the axis, the selection of the metal wire diameter is determined according to the ligament diameter of the surgical object, the chitosan nanofibers are wound around the metal wire to form a preassembled core fiber, and finally the shell layer formed by the hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber is coated on the outside to form a nano-power generation absorbable material, which can also be called an artificial neural prosthesis ACL enhancement cable. It generates electricity through the triboelectric effect generated by the outer layer of chitosan nanofibers and hydroxybutyric acid-hydroxyvaleric acid copolyester and performs electrical stimulation through metal electrodes, promotes cell proliferation and provides a good nerve regeneration promotion effect, and continuously generates electrical stimulation to reconstruct neural pathways. The diameter of the artificial nerve prosthesis ACL reinforcement cable is 400-600 μm, the elongation at break is 10-20%, the tensile strength is 40-60 MPa, and the output electrical stimulation voltage is 0.5-2V.
[0054] As an embodiment of the present invention, a method for providing chitosan nanofibers includes: preparing a chitosan precursor solution; injecting the chitosan precursor solution into a first spinning machine for electrostatic spinning. In other words, chitosan nanofibers are prepared by electrostatic spinning.
[0055] Specifically, the method for preparing a chitosan precursor solution comprises: adding chitosan powder with a molecular weight of 100000-110000 and a deacetylation degree of ≥95% to a dichloromethane-trifluoroacetic acid mixed solvent at a mass concentration of 8-10wt% until it is completely dissolved. The applied positive and negative voltages for electrospinning are 8.5-9.5kV, and the distance between the positive and negative electrodes is 15-20cm; the feeding speed of the chitosan precursor solution is 0.025-0.035mL / h; the metal funnel speed of the first spinning machine is 600-800 rpm, and the winding roller speed of the first spinning machine is 25-30 rpm. By controlling the molecular weight of chitosan and the mass concentration of chitosan in the mixed solvent to 8wt%, uniform nanofibers can be formed after electrospinning; by controlling the external positive and negative voltages during electrospinning, the chitosan precursor solution is stretched into fibers; by controlling the feed rate of the chitosan precursor solution, the morphology of the nanofibers is ensured. When the feed rate is too low, the solution flowing into the needle does not have time to keep up with the jet being ejected, making it difficult to form continuous fibers. When the flow rate is too high, the jet does not have time to dry and falls on the collector, which easily leads to bead defects or the formation of ribbon fibers.
[0056] As an embodiment of the present invention, the metal wire is a magnesium wire.
[0057] As an embodiment of the present invention, a method for providing a hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber includes: adding dry and anhydrous hydroxybutyric acid-hydroxyvaleric acid copolyester powder to chloroform until it is completely dissolved to obtain a hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution; injecting the hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution into a second spinning machine for melt spinning. Before preparing the hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution, the hydroxybutyric acid-hydroxyvaleric acid copolyester powder can be dried. Usually, the hydroxybutyric acid-hydroxyvaleric acid copolyester powder is placed in an oven at 100°C for 4 hours to remove moisture. After obtaining the hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution, melt spinning is performed. The processing temperature of melt spinning is 230-260°C; the feed rate of the hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution is 0.25-0.3kg / h; the winding machine speed of the second spinning machine is 20-25m / min. By setting the above parameters, a uniform nanofiber material can be obtained. Specific embodiments
[0059] The following examples further illustrate the absorbable nano-power-generating material and its preparation method, as well as the absorbable nano-power-generating ligament repair prosthesis having the absorbable nano-power-generating material.
[0060] Example 1
[0061] S1, preparing chitosan nanofibers: adding chitosan powder with a molecular weight of 100000 and a deacetylation degree of ≥95% to a dichloromethane-trifluoroacetic acid mixed solvent at a mass concentration of 8wt% until completely dissolved to obtain a chitosan precursor solution, injecting the chitosan precursor solution into a first spinning machine for electrostatic spinning to obtain chitosan nanofibers, the external positive and negative voltages of electrostatic spinning are 9kV, and the distance between the positive and negative electrodes is 15cm; the feeding rate of the chitosan precursor solution is 0.025mL / h; the rotation speed of the metal funnel of the first spinning machine is 600 rpm, and the rotation speed of the winding roller of the first spinning machine is 25 rpm;
[0062] S2, winding chitosan nanofibers around metal wires to form preassembled core fibers;
[0063] S3, preparing hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber: adding dry and anhydrous hydroxybutyric acid-hydroxyvaleric acid copolyester powder into chloroform until it is completely dissolved to obtain hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution, injecting the hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution into a second spinning machine for melt spinning, the processing temperature of the melt spinning is 230° C.; the feeding speed of the hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution is 0.25 kg / h; the winding machine speed of the second spinning machine is 20 m / min;
[0064] S4, coating the hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber on the preassembled core fiber to form a nano-power generation absorbable material.
[0065] The damaged ligament area 3 of the New Zealand white rabbit is sutured to the main body 100 using the absorbable nano-power generation material of Example 1 as a traction line, wherein the traction line for suturing the femoral connection section 111 of the femoral support part 110 in the main body 100 and the ligament defect area 3 is a femoral traction line 210, and the femoral traction line 210 passes through the ligament defect area 3 and is connected to the tibial fixation section 122 of the tibial support part 120. The traction line for suturing the tibial connection section 121 of the tibial support part 120 in the main body 100 and the ligament defect area 3 is a tibial traction line 220, and the tibial traction line 220 passes through the ligament defect area 3 and is connected to the femoral fixation section 112 of the femoral support part 110.
[0066] Comparative Example 1
[0067] The difference from Example 1 is that the ligament of the New Zealand white rabbit is not damaged, that is, the ligament is not sutured using silk thread and a main body, and the incision site is the same as that in Example 1, and only the wound at the incision site is sutured after incision.
[0068] Comparative Example 2
[0069] The difference from Example 1 is that after the ligament of the New Zealand white rabbit was incised, the damaged ligament was sutured with ordinary absorbable sutures, and the incision site was the same as that in Example 1.
[0070] Performance Verification
[0071] (1) Mechanical properties
[0072] The New Zealand white rabbit animal models of the above-mentioned Example 1 and Comparative Examples 1-2 were subjected to knee biomechanical tests to test the maximum force, stiffness, and deformation at fracture, and the results are shown in the figure. The results show that the maximum force, stiffness, and deformation of Example 1, Comparative Example 1, and Comparative Example 2 are substantially the same, that is, the mechanical properties of the main body 100 and the damaged ligament sutured by the nano-power-generating absorbable material of Example 1 can meet the standard requirements, and the nano-power-generating absorbable material plays a role in repairing ACL damage.
[0073] (2) Absorbability
[0074] The photographs of Example 1 using the absorbable nano-power-generating material as a traction line to suture the damaged ligament and the main body 100 of the New Zealand white rabbit were recorded. After 1.5 months of self-healing, the surgical site was cut open to verify the absorption of the absorbable nano-power-generating material. The results are as follows Figure 2 As shown, the results show that the absorbable nano-power-generating material of Example 1 of the present invention has been absorbed, and the absorption performance of the absorbable nano-power-generating material of Example 1 of the present invention is better than the nano-power-generating wire for ligament repair in clinical application.
[0075] (3) Interference with the brain
[0076] The brain fMRI detection and data processing of the New Zealand white rabbit animal model of the above Example 1 and Comparative Examples 1-2 are as follows: Figure 3-Figure 7 As shown, the results show that the interference of the nano-power-generating absorbable material in Example 1 on the brain is roughly the same as that in Comparative Example 1, and the interference of the nano-power-generating absorbable material in Example 1 on the brain is better than that in Comparative Example 2, that is, the nano-power-generating absorbable material in Example 1 has a good repair effect.
[0077] In addition, the MPA multi-channel biological signal analysis system was used to record the amplitude and latency of the sciatic nerve action potential of the New Zealand white rabbit animal model of the above Example 1 and Comparative Examples 1-2. The results are as follows: Figure 8 As shown, the action potential amplitudes corresponding to Comparative Example 1, Comparative Example 2, and Example 1 are (47.33±9.72) mV, (31.13±8.26) mV, and (34.36±12.56) mV, respectively; the group latencies corresponding to Comparative Example 1, Comparative Example 2, and Example 1 are (0.97±0.14) ms, (1.04±1.42) ms, and (1.19±0.18) ms, respectively. In other words, after the ordinary silk thread of Comparative Example 2 was used to repair the ACL, the action potential amplitude of the sciatic nerve did not return to the normal level, but the latency returned to the normal level; after the nano-power-generating absorbable material of Example 1 was used to repair the ACL, the action potential amplitude of the sciatic nerve returned to the normal level, but the latency did not return to the normal level.
[0078] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A nanometer power generation absorbable material, characterized in that: The nanometer power generation absorbable material has a diameter of 400-600 μm, an elongation at break of 10-20%, a tensile strength of 40-60 MPa, and an output electrical stimulation voltage of 0.5-2 V; The preparation method of the nanometer power generation absorbable material is as follows: chitosan nanofibers are wound around metal wires to form preassembled core fibers; and hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fibers are coated on the preassembled core fibers to form the nanometer power generation absorbable material.
2. An absorbable nano-electric ligament repair prosthesis, characterized in that: include: main body; The stretching part is the absorbable nano-power generation material according to claim 1, and is used to sew the main body and the ligament defect area.
3. The absorbable nano-electric ligament repair prosthesis according to claim 2, characterized in that: The body is configured to pass through the ligament defect area and form two support parts located on both sides of the ligament defect area, each of the support parts includes a connecting section connected to the ligament defect area and a fixing section extending in a direction away from the ligament defect area, and the fixing section is configured to be connected to the bone; The stretching portion includes two traction lines respectively connecting the two support portions, one of the traction lines is used to sew the connecting segment of one of the support portions to the ligament defect area, and passes through the ligament defect area to be connected to the fixed segment of the other support portion, and the other traction line is used to sew the connecting segment of the other support portion to the ligament defect area, and passes through the ligament defect area to be connected to the fixed segment of one of the support portions.
4. A method for preparing the nanometer power generation absorbable material according to claim 1, characterized in that: The steps include: Providing chitosan nanofibers; Winding the chitosan nanofibers onto a metal wire to form a preassembled core fiber; Providing hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber; The hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber is coated on the preassembled core fiber to form the nano-power generation absorbable material.
5. The preparation method according to claim 4, characterized in that: The method for providing the chitosan nanofibers comprises: preparing a chitosan precursor solution; The chitosan precursor solution is injected into a first spinning machine for electrostatic spinning.
6. The preparation method according to claim 5, characterized in that: The method for preparing a chitosan precursor solution comprises: Chitosan powder with a molecular weight of 100000-110000 and a deacetylation degree of ≥95% is added into a dichloromethane-trifluoroacetic acid mixed solvent at a mass concentration of 8-10wt% until it is completely dissolved.
7. The preparation method according to claim 5, characterized in that: The external positive and negative voltages of the electrospinning are 8.5-9.5 kV, and the distance between the positive and negative electrodes is 15-20 cm; The feeding rate of the chitosan precursor solution is 0.025-0.035 mL / h; The rotation speed of the metal funnel of the first spinning machine is 600-800 rpm, and the rotation speed of the winding roller of the first spinning machine is 25-30 rpm.
8. The preparation method according to claim 4, characterized in that: The metal wire is a magnesium wire.
9. The preparation method according to claim 4, characterized in that: The method for providing a hydroxybutyric acid-hydroxyvaleric acid copolyester sheath fiber comprises: Adding dry and anhydrous hydroxybutyric acid-hydroxyvaleric acid copolyester powder into chloroform until it is completely dissolved to obtain a hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution; The hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution is injected into a second spinning machine for melt spinning.
10. The preparation method according to claim 9, characterized in that: The processing temperature of the melt spinning is 230-260°C; The feeding rate of the hydroxybutyric acid-hydroxyvaleric acid copolyester spinning solution is 0.25-0.3 kg / h; The winding machine speed of the second spinning machine is 20-25m / min.
Citation Information
Patent Citations
Degradable artificial ligament for repairing neural circuit and preparation method of degradable artificial ligament
CN115154666A
System and method for damaged tissue repair and system and method for cruciate ligament reconstruction
CN115944337A